Construction of the “Mission poCELLble” -Cellular Structure and Function: A Strategic Intervention Material (SIM) for Grade 7 Biology - Cabildo, Lucrecia (IJCER (International Journal of Chemistry Education Research), 2024)
This study aimed to address the persistent challenges of low student mastery in Grade 7 Biology by constructing and validating a Strategic Intervention Material (SIM) titled "Mission poCELLble" – Cellular Structure and Function. The development process was driven by the urgency to provide targeted support for students struggling with key concepts in cellular biology. A Strategic Intervention Material (SIM) for grade seven biology was the main objective of this study. The SIM was meticulously crafted based on the identified least mastered skills and the Department of Education's standard criteria for SIM construction. This research followed the input-process-output model of developing instructional material, utilizing two sets of questionnaires: one set for five identified experts and one for teacher and student users, each containing 19 statements tailored to their respective roles. Data analysis informed the construction of the SIMs, including identifying least mastered skills, assessing student-teacher agreement with the Kappa Measure, and measuring expert and readability levels with Cronbach's alpha and Flesh-Kincaid Reading Ease.The results revealed that the SIM content, pedagogical and technical aspects were “very evident” as rated by the experts. The internal consistency between responses are rated as “good”. These findings suggest the potential of the "Mission poCELLble" SIM as a valuable tool for intervention purposes in Grade 7 Biology classrooms. Further research is recommended to assess the SIM's effectiveness in improving student learning outcomes.